The Legacy of Sickness Behaviors - Kelley, Keith W.; Kent, Stephen (Frontiers in Psychiatry, 2020)
Systemic infections of all types lead to a syndrome known as sickness behavior. Changes in the behavior of febrile humans and animals formed the original basis for this concept. In addition to fever, sickness behavior now includes sleep disruption, anorexia, cognitive and memory deficits and disorientation. The brain mediates this entire cluster of symptoms, even though most major infections occur outside the brain. The true importance of sickness behavior is not the numerous discoveries of symptoms that affect all of us when we get sick. Instead, the legacy of 30 years of research in sickness behavior is that it established the physiologic importance of reciprocal communication systems between the immune system and the brain. This conceptual advance remains in its infancy.